The local limit theorem of large deviations for multiplicative functions - Skrabutėnas, Rimantas (Lietuvos matematikos rinkinys, 2001)
In the present paper we continue investigation of the local distribution of multiplicative arithmetic functions from the class M(G). A local theorem of large deviations is obtained.